Comparison of pharmacological activity of hawthorn fruits preparations - Vladimir A. Kurkin; Elena N. Zaitceva; Elena V. Avdeeva; Viktoriya V. Stenyaeva; Ilnur Kh. Shaikhutdinov; Alina V. Zhdanova (Наука и инновации в медицине, 2020)
Objectives a comparative study of antidepressant activity and diuretic action of water and water-alcohol preparations of the fruits ofCrataegus sanguinea Pall.andCrataegus submollis Sarg.